Older By Sasha Sloan Perspective Semiotic Roland Barthes and Islamic Family Law - Fauzan, Ahmad; Syauqi, Muammar (IJLHE: International Journal of Language, Humanities, and Education, 2025)
Lyrics in music are a form of communication that need to be interpreted. Uncovering their meaning naturally requires a method called semiotics. Analyzing the lyrics of “Older” by Sashara is essential to grasp the message intended. This study is a literature review discussing the song “Older” from Roland Barthes' semiotics perspective and Islamic family law within the concept of a sakinah family. The denotative meaning of “Older”s lyrics relates to aging. The connotative meaning suggests that aging should be accompanied by maturity in facing life, especially in family life. The myth in the song pertains to the dynamics of family life. The Islamic family law perspective is used as a specific framework within the social approach to Muslim communities. This song offers an illustration of how to realize a sakinah (happy) family when interpreted wisely and learned from the song.